Causes of unsatisfactory results after laparoscopic hiatal hernia repair - A. G. Grintcov; R. V. Ishchenko; I. V. Sovpel; O. V. Sovpel; V. V. Balaban (Исследования и практика в медицине, 2021)
Purpose of the study. To analyze the causes of unsatisfactory results after laparoscopic repair of hiatal hernia, complicated by gastroesophageal reflux disease. Materials and methods. A retrospective analysis of the treatment of 171 patients, who underwent laparoscopic hiatal hernia repair for the period 2009–2018 was carried out. In case of hiatal hernia defect 5 or more cm 29 (29.6%) of 98 patients performed the mesh hiatal hernia repair. Nissen fundoplication was used in 109 (63.7%) patients, Toupet fundoplication – in 62 (36.3%) patients. Intra‑abdominal esophagus segment length was measured intraoperatively after mediastinal mobilization, and after desuflation before the creation of the fundoplication wrap. In the long‑term postoperative period in patients, who did not have complaints the length of fundoplication wrap was measured. The causes of reoperations were analyzed. Results. In the long‑term period, recurrence was noted in 34 (19.9%) patients, persistent dysphagia was noted in 10 (5.8%) patients, the overall unsatisfactory result was 22.8% (39 patients). 26 (15.2%) patients were unsatisfied their present condition (according to the GERD‑HRQL questionnaire). The use of mesh repair in comparison with simple suture repair not affected on frequency of recurrence in case of hernia 5 cm or more – 4 (13.8%) versus 14 (20.3%), CI: 0.19–2.1, p=0.44. The choice of fundoplication method (Nissen or Toupet) not affected on recurrence rate – 17.4% (19/109) versus 24.2% (15/62), CI: 0.71–3.24, p=0.39. The length of the fundoplication wrap at uppercontrastradiographswas 3.2 cm (2.3–3.7 cm). Intraoperativly after desuflation, the shortening of the esophagus was 1.3 cm (0.5–2 cm). 12 (7%) patients were reoperated. The shortening of the esophagus was revealed in all cases of reoperations. Conclusion. Unreduced during the first operation short esophagus, which was diagnosed during all reoperations, was one of the possible factors, affecting the frequency of recurrence in the long term. Further studies are needed to evaluate the use of lengthening esophagus procedure on the long-term outcomes.